Soft Power a La Russe: Making Sense of Russia’s Soft Power Approach. - Bogdanova, Sofiia (My University, 2016)
In 1990, Joseph Nye coined the term “soft power” to define co-optive power that is based on attraction rather than coercion. For quite a long time it was believed that soft power was a prerogative of Western-style democracies as they were closest to the values constituting the basis of Nye’s classical soft power concept. Nye remained skeptical over the ability of hard states to produce soft power. However, nowadays all types of governments including non-democratic ones turn to soft power. In Russia soft power has become a priority since early 2000s, making it no longer a newcomer in this regard. Russia’s experience shows an alternative way to wield soft power. Thus, the aim of this thesis is to understand how Nye’s classical soft power concept is re-conceptualized within the Russian context. In doing so it promises to go beyond a Western-centric understanding of soft power and to contribute to a discussion on how hard states adopt and adjust soft power to their needs. Discourse analyses is employed as a specific method of qualitative research to decode the meaning attributed to the concept of soft power within Russian official soft power discourse. The sources that are analyzed include official documents, speeches, articles, and interviews by key Russian political figures (V. Putin, D. Medvedev, S. Lavrov, K. Kosachev, V. Nikonov). The timeframe of analyses focuses on the period from 2012 when the term ‘soft power’ first appeared in Russian official discourse to the end of 2015, one year after a striking event for Russian soft power - the annexation of Crimea. The main findings of this thesis support the initial assumption that Russia’s soft power is more than just “an act of mimicry” or an attempt to catch up with the West. Approaching Nye’s concept through the prism of own historical, political and socio-economic background, Russian authorities develop a significantly different de-Westernized understanding of soft power. First, while the aim of Nye's concept is to make a country attractive, Russian soft power concentrates on elaborating Russia's political stance and actions in order to withstand the discrepancy between Russia’s reality and its international perception. Second, it is revealed that Russia understands and articulates soft power through four main groups of narratives - centrality of the state, pragmatic instrumental approach, geopolitical concerns and reactive argumentation. Finally, it is suggested that those narratives appear to be more universal than the Western values that backbone Nye's classical soft power concept and their further studies within other contexts could extend academic knowledge on the soft power concept.